Pengaruh Work Life Balance terhadap Work Engagement pada Perawat Lansia - Noli Saraswati Dewi; Anna Rozana (Jurnal Riset Psikologi, 2024)
Abstract. Work engagement is a positive state of mind and fulfillment related to work that has the characteristics of vigor, dedication, and absorption (Shaufeli et al., 2002). One of the factors that can enhance work engagement is work-life balance. Work-life balance is the effort to balance two or more roles that one engages in (Fisher, 2009). This study aims to determine the influence of work-life balance on work engagement among elderly caregivers at Nursing Homes in the city of Bandung. The measurement tools used are the Work-Life Balance Scale (WLBS), referring to Fisher et al.'s theory (2009), adapted by Gunawan et al. (2019), and the Utrecht Work Engagement Scale-9 (UWES-9), referring to Schaufeli et al.'s theory (2002), adapted by Kristiana et al. (2018). The sampling technique used is saturation sampling with a total of 37 respondents. The method used in this study is a quantitative causal method, employing multiple linear regression analysis techniques. The results of this study indicate that, simultaneously, work-life balance has a significant effect on work engagement, accounting for 60.4%. Meanwhile, on a partial basis, the dimension of Personal Life Interference with Work (PLIW) contributes to an effect of 34.8%, and the dimension of Personal Life Enhancement of Work (PLEW) contributes to an effect of 18.4%. Abstrak. Work Engagement merupakan suatu keadaan pikiran yang positif serta pemenuhan yang berkaitan dengan pekerjaan yang memiliki karakteristik vigor, dedication, dan absorption (Shaufeli et al., 2002). Salah satu faktor yang dapat meningkatkan work engagement yaitu work life balance. Work life balance adalah upaya menyeimbangkan dua peran atau lebih yang dijalani (Fisher, 2009). Penelitian ini bertujuan untuk mengetahui pengaruh work life balance terhadap work engagement pada perawat lansia di Panti Jompo Kota Bandung. Alat ukur yang digunakan yaitu Work Life Balance Scale (WLBS) yang mengacu pada teori Fisher et al., (2009) yang diadaptasi oleh Gunawan et al., (2019) dan Utrecht Work Engagement Scale-9 (UWES-9) yang mengacu pada teori Schaufeli et al., (2002) yang diadaptasi oleh Kristiana et al., (2018). Teknik sampling yang digunakan adalah sampling jenuh dengan responden sebanyak 37 orang. Metode yang digunakan dalam penelitian ini yaitu metode kuantitatif kausalitas dengan menggunakan teknik analisis regresi linear berganda. Hasil penelitian ini menunjukkan bahwa, secara simultan work life balance berpengaruh signifikan terhadap work engagement sebesar 60.4%. Sedangkan secara parsial yang memberikan pengaruh yaitu dimensi Personal Life Interference with Work (PLIW) sebesar 34.8% dan dimensi Personal Life Enhancement of Work (PLEW) sebesar 18.4%.